Knowledge of COVID-19 symptoms, transmission, and prevention: Evidence from health and demographic surveillance in Southern Mozambique. - Ariel Nhacolo; Zachary J Madewell; Jonathan A Muir; Charfudin Sacoor; Elisio Xerinda; Teodimiro Matsena; Edgar Jamisse; Quique Bassat; Cynthia G Whitney; Inacio Mandomando; Solveig A Cunningham (Public Library of Science (PLoS), 2023)
Understanding community members' knowledge of SARS-CoV-2 transmission and prevention is essential for directing public health interventions to reduce disease spread and improve vaccination coverage. Here, we describe knowledge of COVID-19 transmission, prevention, and symptoms among community residents in Mozambique. We conducted a cross-sectional survey among 33,087 households in a Health and Demographic Surveillance System in Manhiça, Mozambique. Participants were recruited in April 2021 before the Delta variant wave to the peak of Omicron cases in February 2022. Principal components analysis was used to create scores representing knowledge of COVID-19 symptoms, transmission, and prevention. Multiple imputation and quasi-Poisson regression were used to examine associations between demographic characteristics and sources of COVID-19 information, and knowledge of COVID-19 symptoms, transmission, and prevention. We examined whether sources of COVID-19 information mediated the relationship between educational attainment and knowledge of symptoms, transmission, and prevention. Across this rural community, 98.2%, 97.0%, and 85.1% of respondents reported knowing how COVID-19 could be prevented, that SARS-CoV-2 can cause disease, and how SARS-CoV-2 is transmitted, respectively. The most recognized COVID-19 symptoms were cough (51.2%), headaches (44.9%), and fever (44.5%); transmission mechanisms were saliva droplets (50.5%) or aerosol (46.9%) from an infected person; and prevention measures were handwashing (91.9%) and mask-wearing (91.8%). Characteristics associated with greater knowledge of symptoms, transmission, and prevention included having at least primary education, older age, employment, higher wealth, and Christian religion. Respondents who had experienced COVID-19 symptoms were also more likely to possess knowledge of symptoms, transmission, and prevention. Receiving information from television, WhatsApp, radio, and hospital, mediated the relationship between educational attainment and knowledge scores. These findings support the need for outreach and for community-engaged messaging to promote prevention measures, particularly among people with low education.